Flexible inkjet printed high-k HfO2-based MIM capacitors. Issue 9 (8th February 2016) - Vescio, G.; López-Vidrier, J.; Leghrib, R.; Cornet, A.; Cirera, A.
Abstract : The soaring global demand for flexible, wearable and transparent devices has created an urgent need for new fabrication technologies that are both cost-competitive and eco-friendly. Abstract : The soaring global demand for flexible, wearable and transparent devices has created an urgent need for new fabrication technologies that are both cost-competitive and eco-friendly. Printed electronics holds the promise of enabling low-cost, scalable solutions exploiting the ability of innovative materials to be used as processed inks onto a large area substrate. In this article, we demonstrate the direct drop-on-demand inkjet printing technology as a viable method for the fabrication of fully-printed metal–insulator–metal capacitors on a flexible substrate (Kapton®), where the high- k hafnium oxide (HfO2 ) was selected as the dielectric. After a low-temperature annealing process, the deposited nanoparticle (NP)-based ink of HfO2 showed high homogeneity and good integrity of the printed thin film by microscopy and spectroscopy studies. The fully-printed capacitors were characterized by field-emission scanning and transmission electron microscopies. X-ray diffraction patterns, as well as Raman scattering and Fourier-transform infrared spectra, revealed the presence of a polycrystalline solid layer, without solvent organic ink remains. The bonding structure of the HfO2 layer and the interface with the Ag electrode was studied by X-ray photoelectron spectroscopy. The good performance of the thin film was proved by its relative permittivity, k = 12.6, and dielectric loss tangent, tan  δ = 0.0125 at 1 MHz. Finally, the electrical current density–voltage and capacitance–voltage measurements have been studied in the frequency range from 10 kHz to 1 MHz. The obtained results indicate that MIM capacitors based on inkjet-printed flexible HfO2 NPs work properly within the ITRS 2016 roadmap requirements.